DMOADs and DMARDs in the treatment of patients with joint and spine diseases - O. A. Shavlovskaya (Фармакоэкономика, 2024)
The data on the classification of drugs, which are prescribed for the treatment of patients with joint and spine diseases, such as osteoarthritis (OA) and rheumatoid arthritis (RA), are presented. The groups of drugs widely used in clinical practice are disease-modifying osteoarthritis drugs (DMOADs) and disease-modifying antirheumatic drugs (DMARDs). To help the practitioner, consolidated information is provided on the main differences between these groups according to the mechanism of action (immunomodulatory vs. immunosuppressive) and the main indications for use (autoinflammatory joint diseases (OA) vs. autoimmune joint diseases (RA, psoriatic arthritis, ankylosing spondyloarthritis)). The material of the article is focused on the clinicians to help them make a right choice of OA therapy, and to identify the problem of drug choice in RA. Information about the possibility of using nutritional support in patients with OA is presented.